A systematic review to identify how the current clinical trials landscape reflects the James Lind Alliance top 10 research priorities for cystic fibrosis - Kalaitzis, I.S.; Rowbotham, Nicola J.; Smith, S.J.; Smyth, A.R. (Unpublished, 2018)
This is a protocol to describe the methodology for a systematic review of clinical trials registries to identify intervention trials in the treatment of CF and map them to priorities for CF research.